Antecedents of Total Factor Productivity Change: empirical evidence from the Chinese banking sector - Sufian, Fadzlan (Springer Verlag, 2009)
By applying the non-parametric Malmquist Productivity Index (MPI) method, this paper attempts to investigate the sources of productivity changes of China’s State Owned Commercial Banks (SOCBs) and Joint Stock Commercial Banks (JSCBs) during the period 2000–2005. The empirical findings suggest that the China banking sector has exhibited productivity progress attributed to the increase in efficiency. The empirical findings suggest that the SOCBs and the JSCBs have exhibited productivity progress of 0.2 and 1.3%, respectively.